HUBUNGAN ANTARA PENGETAHUAN TENTANG PERAWATAN ORGAN REPRODUKSI DENGAN TINDAKAN PERSONAL HYGIENE PADA REMAJA PUTRI DI SMP 2 SOCAH - Zuryati M.Kes (NHM PRESS, 2019)
Informatio relates to reproductive health from parents and schools is not enough. It was obtaind that teenagers has lack knowledge of reproductive health about personal hygiene. A preliminary study of 10 teenage girls found that 6 teenage girls had less personal hygiene measures. The purpose of the study was to analyze the relationship between knowledge about reproductive organs treatment with personal hygiene actions in teenagers in SMP 2 Socah. The method used in this study was analytical with cross sectional approach. The population was 32 girls and the sample was 30 girls in class VII and VIII in SMP 2 Socah. The sampling technique used is Proportionate Stratified Random Sampling. The independent variable knowledge of reproductive organ care, and the dependent variable of personal hygiene action. The research instrument used questionnaire, then tested with Pearson statistical test with α = 0,05. The results showed that girls of grade VII and VIII mostly had sufficient knowledge about reproductive organ care (53%), while half of the girls were taking enough and less hygiene action (50%). Pearson statistical test results obtained ρ value 0.001 <α 0.05 means Ho rejected there was a relationship between knowledge about reproductive organs treatment and personal hygiene actions teenagers in SMP 2 Socah. Efforts are used to improve knowledge about reproductive organ care by giving counseling as well as expected teenagers add information about reproduction organ care by accessing information from various source in order to prevent the happening of problem at reproduction organ